Microwave-assisted synthesis of well-shaped UiO-66-NH2 with high CO2 adsorption capacity. (February 2018) - Huang, Aisheng; Wan, Linlin; Caro, Jürgen
Graphical abstract: Highlights: Well-shaped UiO-66-NH2 was prepared through microwave heating in a short time. Addition of HAc improves crystallinity and CO2 adsorption capacity of the UiO-66-NH2 . UiO-66-NH2 prepared by microwave heating shows a higher CO2 /N2 adsorption selectivity. Abstract: In a detailed study, the influence of microwave irradiation, synthesis time and temperature, addition of acetic acid (HAc) as a modulator on the morphology, crystallinity and stability of UiO-66-NH2 is investigated to develop a reliable and reproducible strategy for the preparation of well-shaped UiO-66-NH2 . The UiO-66-NH2 were characterized by powder X-ray diffraction (PXRD), field emission scanning electron microscopy (FESEM), thermogravimetric analysis (TGA), and gas adsorption. It is found that well-shaped UiO-66-NH2 with a high CO2 adsorption capacity can be synthesized in a short time by microwave heating. The UiO-66-NH2 crystals synthesized by microwave heating are of high quality and show a superior CO2 adsorption capacity (5.8 mmol/g at 273k and 1 bar) due to the strong interactions between the −NH2 group and CO2 . The CO2 /N2 selectivity of the obtained UiO-66-NH2 at 298 K and 1 bar is 66, which is much higher than that of the pristine UiO-66 of 17.8.